Educational Values of the Dream and Reality Psychoanalysis In â€œSang Pemimpiâ€ (the Dreamer), a Novel by Andrea Hirata - Muhammad Nasir (AT-TA'LIM, 2015)
This article tries to look at psychoanalysis study of a novel concerning on the dream and reality in Sang Pemimpi (the Dreamer) by Andrea Hirata. In general, his work portrays mostly about the condition and situational life of Belitung community. Here, Andrea shows his ability as the representative of Belitung's young generation succeeded in fulfilling his dream by explaining the real life of the people in his hometown and villages having bitter experience values in the rich environment. Besides, he tries to describe the difficult life faced by the villagers. The dream in this novel is not only his, but also all dreams of the Belitung community as the manifestation of their life condition comparing to other areas or provinces in the Indonesia. Further, through this novel (work), it is implied an important massage directed to both Indonesian authority and Belitung mayor in order to be able to increase the level of education of grass root community, especially for those who live in the remote area or a very isolated area, such as Belitung. This is the real dream of all participants in the island which remains unsolved.